Postbiotics as effective and safe "vaccines" against various respiratory diseases: literature review - Poniewozik, Paweł; Pernal, Maja; Mioduszewska, Joanna; Rot, Paweł; Poniewozik, Piotr; Dziuba, Natalia; Sim, Aleksandra; Zuzak, Andrzej; Roguska, Zofia; Grabowski, Krzysztof (Quality in Sport, 2026)
Background: Respiratory diseases, including COPD, asthma, and allergic rhinitis, pose a significant health and economic burden, prompting the search for new preventive and therapeutic strategies. Increasing attention is paid to microbiome-based therapies and the gut-lung axis as targets for immunomodulatory interventions. Postbiotics - defined as non-viable microorganisms or their components that exert beneficial biological effects - have emerged as a promising area of research. Aim of the study: This study presented the current state of knowledge regarding postbiotics and assessed their potential in the prevention and treatment of respiratory diseases, with particular emphasis on their mechanisms of action. Methodology: The review was conducted using PubMed and supplementary Google Scholar. Studies from 2012 to 2026 were analyzed. Results: Postbiotics demonstrate multiple mechanisms of action, including modulation of the immune response, regulation of cytokine production, influence on the Th1/Th2 balance, and enhancement of epithelial barrier integrity. Experimental and clinical evidence suggests that postbiotics may reduce the frequency and severity of infections, decrease exacerbations of chronic respiratory diseases, and support the treatment of atopic and neaplastic conditions. In addition, they have a favorable safety profile, potentially better than probiotics, especially in populations with compromised immunity. Conclusion: Postbiotics represent a diverse and promising group of compounds with significant potential for both preventive and therapeutic applications in respiratory diseases. However, further well-designed, large-scale clinical trials are necessary to confirm their efficacy and safety.